2011
DOI: 10.1016/j.media.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Automated kymograph analysis for profiling axonal transport of secretory granules

Abstract: This paper describes an automated method to profile the velocity patterns of small organelles (BDNF granules) being transported along a selected section of axon of a cultured neuron imaged by time-lapse fluorescence microscopy. Instead of directly detecting the granules as in conventional tracking, the proposed method starts by generating a two-dimensional spatiotemporal map (kymograph) of the granule traffic along an axon segment. Temporal sharpening during the kymograph creation helps to highlight granule mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…3 A and B). Kymographs generated from time-lapse images revealed the behavior of individual mitochondria within an axon (50-150 μm in length) (38). Stationary mitochondria appear as vertical lines, and moving mitochondria appear as diagonal lines, with the slope representing the velocity (Fig.…”
Section: Loss Ofmentioning
confidence: 99%
“…3 A and B). Kymographs generated from time-lapse images revealed the behavior of individual mitochondria within an axon (50-150 μm in length) (38). Stationary mitochondria appear as vertical lines, and moving mitochondria appear as diagonal lines, with the slope representing the velocity (Fig.…”
Section: Loss Ofmentioning
confidence: 99%
“…Dysfunctions in this pathway can be detrimental to the cell’s structural integrity and its overall ability to function [4]. Recently, many vesicle classes have been identified that are transported within axons [5][7], but their spatial and temporal motility kinetics remain elusive, mainly due to the lack of a suitable model system for such analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This algorithm is particularly effective for these cases. Regardless of their origins, though, there have been a number of successful efforts made to automate the detection of a particle's path from a kymograph (Mukherjee et al, 2011;Welzel et al, 2009;Zhang et al, 2010) but the methodology to create a kymograph has remained relatively underdeveloped, often at the expense of efficiency and accuracy.…”
Section: Discussionmentioning
confidence: 99%